Kombucha tea as an anti-hyperglycemic agent in humans with diabetes – a randomized controlled pilot investigation - Mendelson, Chagai; Sparkes, Sabrina; Merenstein, Daniel J.; Christensen, Chloe; Sharma, Varun; Desale, Sameer; Auchtung, Jennifer M.; Kok, Car Reen; Hallen-Adams, Heather E.; Hutkins, Robert (Frontiers in Nutrition, 2023)
Introduction: Kombucha is a popular fermented tea that has attracted considerable attention due, in part, to its suggested health benefits. Previous results from animal models led us to hypothesize kombucha may reduce blood sugar levels in humans with diabetes. The objective of this pilot clinical study was to evaluate kombucha for its anti-hyperglycemic activities in adults with diabetes mellitus type II. Methods: The study was organized as a prospective randomized double-blinded crossover study at a single-center urban hospital system. Participants (n = 12) were instructed to consume either a kombucha product or a placebo control (each 240 mL) for 4 weeks. After an 8-week washout period, participants consumed the alternate product. Fasting blood glucose levels were self-determined at baseline and at 1 and 4 weeks during each treatment period. Secondary health outcomes, including overall health, insulin requirement, gut health, skin health, mental health, and vulvovaginal health were measured by questionnaire at the same time points. The kombucha microbiota was assessed by selective culturing and 16S rRNA gene (bacteria) and ITS (fungi) sequencing. Fermentation end products were assessed by HPLC. Statistical significance of changes in fasting blood glucose was determined using paired, two-tailed student’s t-tests. Results: Kombucha lowered average fasting blood glucose levels at 4 weeks compared to baseline (164 vs. 116 mg/dL, P=0.035), whereas the placebo did not (162 vs. 141 mg/dL, P=0.078). The kombucha microbiota, as assessed by cultural enumeration, was mainly comprised of lactic acid bacteria, acetic acid bacteria, and yeast, with each group present at about 106 colony forming units (CFU)/mL. Likewise, 16S rRNA gene sequencing confirmed that lactic acid and acetic acid bacteria were the most abundant bacteria, and ITS sequencing showed Dekkera was the most abundant yeast. The primary fermentation end products were lactic and acetic acids, both less than 1%. Ethanol was present at 1.5% Discussion: Although this pilot study was limited by a small sample size, kombucha was associated with reduced blood glucose levels in humans with diabetes. Larger follow-up studies are warranted.